PELAKSANAAN ASAS MEMPERSULIT TERJADINYA PERCERAIAN PADA PENGADILAN AGAMA PAYAKUMBUH BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Allifa Amelia; Hayatul Ismi; Hengki Firmanda S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Based on General Description Number 4 Letter e Constitution Number 1 Year of 1974 about Marriage found principle sounded, “because the marriage purpose is to form a happy, eternal, and prosperous family then this constitution embraces the principle to complicate divorce occurance to enable divorce there must be certain reasons and it must be in the court”. In year of 2017-November 2019 there was an increase of divorce at Religious Court Payakumbuh. It was caused by many factors. In this case the writing of this undergraduate thesis aims to; first, find out the implementation of principles which complicate divorce occurance at Religious Court Payakumbuh based on Constitution Number 1 Year of 1974 About Marriage; second, find out the effect of principle which complicates divorce occurance on divorce itself at Religious Court Payakumbuh.The type of this research could be categorized into sociological research. This research was conducted at Religious Court Payakumbuh, while the population and sample were the parties related to the problem being investigated. Data collection was done by using interview and literature study techniques. Data analysis used qualitative data analysis and in taking conclusion the author used deductive method.The result of the research and discussion shows that the implementation of principle which complicates divorce occurance at Religious Court Payakumbuh is implemented in accordance with the procedure regulated by the constitution and other rules. Started from the entrance of lawsuit to the court by related parties, the implementation of peace process in each trial, mediation implementation, and argumentation implementation by the parties in the trial. The effect of this principle in Religious Court Payakumbuh is not really significant because even though the implementation has been done as maximal as possible but in the end the decision depends on the heart problem of the related parties.Keywords: The principle of complicating divorce occurance-Divorce-religious court